Shuttle HAT for mild alkene transfer hydrofunctionalization - Tanner C. Jankins; Philip M. Blank; Andrea Brugnetti; Philip Boehm; Françoise A. Aouane; Bill Morandi (Nature Communications)
Abstract Hydrogen atom transfer (HAT) from a metal-hydride is a reliable and powerful method for functionalizing unsaturated C–C bonds in organic synthesis. Cobalt hydrides (Co–H) have garnered significant attention in this field, where the weak Co–H bonds are most commonly generated in a catalytic fashion through a mixture of stoichiometric amounts of peroxide oxidant and silane reductant. Here we show that the reverse process of HAT to an alkene, i.e. hydrogen atom abstraction of a C–H adjacent to a radical, can be leveraged to generate catalytically active Co–H species in an application of shuttle catalysis coined shuttle HAT. This method obviates the need for stoichiometric reductant/oxidant mixtures thereby greatly simplifying the generation of Co–H. To demonstrate the generality of this shuttle HAT platform, five different reaction manifolds are shown, and the reaction can easily be scaled up to 100 mmol.